Can Australia transition to an agroecological future?. Issue 1 (2nd January 2021) - Iles, Alastair
ABSTRACT: Australia faces seemingly impossible barriers to transitioning to agroecology. Nonetheless, many possibilities for a distinctively Australian agroecology exist. Some Australian farmers have helped create methods for rehydrating landscapes, while Indigenous peoples are reclaiming crops and farming methods well-adapted to Australia's diverse regions.To appraise the prospects for agroecological changes in Australia, I modify in two ways the Multi-Level Perspective framework widely used in transitions research. First, I elaborate the notion of lock-ins that impede systemic change.Looking at Australia reveals an array of socio-ecological lock-ins that matter alongside the more familiar political economy lock-ins. These include settler colonialism, climate/environmental change, and scientific & technological priorities. Second, I add 'massification' (or the growth of a movement supporting change toward agroecology) as one possible process for overcoming these lock-ins. I work through several key drivers of the process of taking agroecology to scale to show how agroecological transition might happen.